SHAPING ATTITUDES ABOUT UNIFAST LAW: THE ROLE OF ORGANIZATIONAL LEADERSHIP AND STUDENTS INVOLVEMENT (Lex localis - Journal of Local Self-Government, 2025)
This study sought to examine the attitudes of students benefiting from UniFAST assistance programs. The specific objectives are to: (1) evaluate the level of organizational leadership in shaping students' attitudes toward the UniFAST Law in terms of vision communication, problem-solving, motivation and inspiration, decision-making, confidence and trust, accessibility and communication, positive learning environment, and ethical conduct; and (2) assess the extent of student involvement in shaping their views on the UniFAST Law and the attitudes towards UniFAST Law. The study employed a cross-sectional descriptive survey, with twenty-five (25) UniFAST recipients from Northern Iloilo State University as respondents. Data was collected through a structured questionnaire. The findings show that students generally have a positive perception of organizational leadership's role in shaping attitudes toward the UniFAST Law. Leadership is particularly strong in communication, problem-solving, motivation, decision-making, and ethical conduct, though improvements in student engagement and transparency are needed. Students feel supported and inspired by leadership but desire a greater role in decision-making. Student involvement in the UniFAST scholarship program is moderate, with students fulfilling application requirements and showing enthusiasm for future activities. However, communication and support services could be enhanced to ensure students make full use of available resources. Overall, students value the program's financial support, recognize its effectiveness in helping them complete their studies, and are inclined to recommend it, though awareness of scholarship options could be further improved.